1999
DOI: 10.1046/j.1472-765x.1999.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic resistance of Escherichia coli to various antimicrobial agents requires ppGpp and sigmas

Abstract: GL A ND . 1999. We have examined the effect of a wide range of antimicrobial compounds (antibiotics and biocides) on the growth of various strains of Escherichia coli which vary in their ability to produce ppGpp and s s . We conclude that strains able to synthesize ppGpp, either in a RelA-or SpoT-dependent manner, possess a greater resistance to antimicrobial compounds compared with strains that cannot produce ppGpp. Investigation of an E. coli strain, unable to produce s s , and an isogenic parent strain, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 25 publications
(46 reference statements)
1
39
0
1
Order By: Relevance
“…These results also suggest that the morphological change of the B. abortus spoT mutant may be affected by inhibition of ppGpp synthesis, and ppGpp may activate the transcription of one or more genes including b-lactamase production, and affect an as yet uncharacterized regulatory mechanism related to cell morphology. Greenway & England (1999) reported that E. coli able to synthesize ppGpp, either in a RelA-or SpoT-dependent manner, possesses greater resistance to antimicrobial compounds compared with E. coli mutants that cannot produce ppGpp. E. coli mutants showed a higher sensitivity, as demonstrated by MIC values, for b-lactam antibiotics, polymyxin, gentamicin, 1,2-benzisothiazolin-3-one (BIT) and bronopol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also suggest that the morphological change of the B. abortus spoT mutant may be affected by inhibition of ppGpp synthesis, and ppGpp may activate the transcription of one or more genes including b-lactamase production, and affect an as yet uncharacterized regulatory mechanism related to cell morphology. Greenway & England (1999) reported that E. coli able to synthesize ppGpp, either in a RelA-or SpoT-dependent manner, possesses greater resistance to antimicrobial compounds compared with E. coli mutants that cannot produce ppGpp. E. coli mutants showed a higher sensitivity, as demonstrated by MIC values, for b-lactam antibiotics, polymyxin, gentamicin, 1,2-benzisothiazolin-3-one (BIT) and bronopol.…”
Section: Discussionmentioning
confidence: 99%
“…MICs were measured by using a modified method described previously (Greenway & England, 1999;Mortensen et al, 1986). Antibiotics or biocides were serially diluted twofold in test tubes containing 2 ml final volume Brucella broth, such that the final antibiotic or biocide concentration was reduced from 400 to 0?01 mg ml 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell envelope stress responses have been linked to general stress responses (7) and to the overall homeostasis of gram-positive bacteria (18). Moreover, it has been reported that the intracellular concentration of (p)ppGpp is linked to the intrinsic resistance to antimicrobial agents in bacteria (14,19,20,40). TLC analysis of nucleotide extracts clearly indicated that (p)ppGpp accumulates to significantly high levels in OG1RF cells treated with inhibitory concentrations of vancomycin (Fig.…”
Section: E Faecalis Strains Can Mount a Classic Stringent Responsementioning
confidence: 94%
“…Studies have correlated changes in (p)ppGpp levels to the expression of virulence traits, including stress survival (12,20,25,54), biofilm formation (2,25,46), antibiotic resistance (14,19,20,40), and persistence (5,14,20,21,35,42). In some cases, animal models have been used to provide unequivocal evidence of the role of (p)ppGpp in virulence (6,9,10,16,39,46).…”
mentioning
confidence: 99%
“…This operon (3) regulates the expression of a large number of genes, including those coding for at least one broad-specificity efflux pump (the arcAB efflux pump) (30), which are more strongly expressed under conditions of environmental stress (23). This suggests a direct linkage between environmental stresses, such as those occurring in foods and the domestic environment (3), efflux pump expression, and the development of antibiotic resistance (ABR) (12,14,30).…”
mentioning
confidence: 99%